How Lifelong Learning Shapes The Professional Development Of Staff In Higher Education Institutions. - Owusu-Agyeman, Y. (Emerald Publishing Limited, 2024)
Purpose – As universities find new ways to implement professional development programmes (PDPs), very few scholarly studies have focused on how lifelong learning could serve as a tool to enhance the professional development of staff. To address this knowledge gap, this study aims to examine how the integration of lifelong learning modes into PDPs in a university setting in South Africa could enable professional staff to advance their knowledge and skills. Additionally, the study explores how the different PDPs could be conceptualised by way of lifelong learning to enhance the professional knowledge and competences of staff. Design/methodology/approach – Data were gathered from 41 professional staff in three campuses of the university. The narrative data gathered were evaluated using thematic analysis that consisted of a detailed process of identifying, analysing, organising, describing and reporting the themes that were generated from the data. Findings – Findings suggest that when the university integrates lifelong learning approaches into its professional development programmes, it allows staff to develop their knowledge and skills through diverse learning approaches. When institutions adopt these diverse learning approaches, it enable staff to situate their learning needs along the different lifelong learning modes, negotiate suitable learning modes and flexible schedules with their heads of department, and learn the accepted norms and values of the university. These findings among others lead to further questions about how PDPs could be designed using the three lifelong learning modes to enable staff to prepare adequately for the future of work in higher education. Originality/value – This study contributes to the scholarly discourse on lifelong learning by showing how higher education institutions could design PDPs along formal, informal and non-formal learning approaches to enhance the knowledge and skills of staff.
Research Article
Keywords: Professional Development; Lifelong Learning; Human Capital Theory; Higher Education; Professional Staff